Biosecurity : Understanding, Assessing, and Preventing the Threat - Burnette, Ryan. (Hoboken : Wiley, 2013)
Learn how to assess and prevent biosecurity threats to protect public health and national security With contributions from experts in all facets of biosecurity, this book explains the fundamental elements of biosecurity as well as the related concepts of biosafety and biosurety, detailing how all three concepts fit within the framework of biodefense. Readers are then given the tools needed to assess and prevent biosecurity threats and vulnerabilities. The book explores the nature of biosecurity threats to research laboratories as well as to agriculture, food, and mass transit.
Assessing Biosafety and Biosecurity Risks in Public Health: The Science of BiosecurityIncreasing Security Functions through the Application of Biosecurity to Public Health; Challenges Associated with the International Coordination of Outbreak Response; Biosecurity Impediments to International Health Programs; Conclusion; PART IV BIOSECURITY POLICY, BIOTERRORISM, AND THE FUTURE; CHAPTER 11 Current Efforts to Fortify Biosecurity Policy in the U.S; Introduction; Emerging Policies Limiting Access to Pathogens and Enhancing Laboratory Security; Policies that Focus on Dual-Use Research of Concern.
Evolving Oversight of Synthetic Biology.
Includes bibliographical references and index.
Print version record.
Keywords: Biosecurity; Bioterrorism -- Prevention; Biological weapons -- Safety measures; Biological weapons -- Safety measures; Biosecurity; Bioterrorism -- Prevention; TECHNOLOGY & ENGINEERING -- Industrial Health & Safety; Biological weapons -- Safety measures; Biosecurity; Bioterrorism -- Prevention; Electronic books